PENGARUH TEMAN SEBAYA TERHADAP PEMAHAMAN DIRI PESERTA DIDIK KELAS X SMAN 1 SUNGAI RAYA - Pera, Pera; Purwanti, Purwanti; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractAdolescence is a very potential phase for the growth and development of physical and psychological aspects both in quality and quantity. Because they consider themselves no longer children but people around him still consider themselves immature. However, their behavior is oaften still exlusive and has not shown maturity, which is spread by a strong urge to find and show their teenagers identity often free themselves from their parents and direct attention to the environment outside their families and tend to be more happy with their peers. This study aims to determine the relationship of Peer Social Interaction with Self Understanding Students Class X IPS in SMA Negeri 1 Sungai Raya. The method used is descriptive method and research form using relationship study. The population in this study as many as 164 students and samples 42 students class X IPS. This study uses a quantitative approach. Data collection techniques used indirect communication techniques and data collection tools using questionnaires. Data analysis techniques using the formula percentage and product moment correlation. Based on the results of this study stated that there is a Relationship of Peer Social Interaction With Self Understanding Students Class X IPS at SMA Negeri 1 Sungai Raya which is included in the category of